The Sleeping Beauty Fairy Tale: An Analysis on Propp’s the Functions of Dramatis Personae - Pramudana Ihsan; Wijayadi . (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
ABSTRACTThis paper is aimed at analyzing the sleeping beauty fairy tale using Vladimir Propp’sfunctions of dramatis personae. The analysis utilizes thirty one functions, however, not all that functions occur in a tale. These functions create a main framework in the story (Propp, 1968:25—65). The analysis reveals similarity between The Sleeping Beauty with any other folktale which came from Rusia. There are thirty one functions of dramatis personae which can be distributed into seven spheres of actions. From these seven spheres of actions, there are seven characters that usually appear in the fairy tales. But in The Sleeping Beauty there are only five characters since there is no helper and false hero in this story.Keywords: Sleeping Beauty, functions of dramatis personae, seven spheres of actions